Review: Tipe Salep, Basis Dan Metode Pembuatan Salep - Elpa Giovana Zola; Milla Astari; Lilik Hevi Novisa; Tata Anggraini; Tiara Nabila Putri (Journal of Innovative and Creativity, 2026)
Ointments are semisolid topical preparations designed to prolong drug contact time on the skin surface and provide protective effects against irritation, infection, and wounds. The effectiveness of an ointment is strongly influenced by the selection of an appropriate base and formulation method. This review aims to analyze various types of ointment bases, formulation techniques, and active substances used in recent studies. A total of 40 published journals were examined using keywords such as “ointment formulation,” “ointment base,” and “ointment preparation methods.” The findings show that hydrocarbon bases are the most widely used due to their stability and strong occlusive properties. Absorption bases and water-soluble bases are also commonly applied depending on the physicochemical characteristics of the active ingredient and therapeutic goals. The most frequently used preparation methods are incorporation and fusion, selected based on the heat sensitivity of the active substances. Most active ingredients reviewed were herbal extracts containing antibacterial, anti-inflammatory, antioxidant, and wound-healing properties. Overall, the compatibility between the ointment base, characteristics of the active compound, and the selected formulation method plays a crucial role in achieving stable, homogeneous, and effective preparations. This review highlights the high potential of natural-based ointments as safe and effective topical formulations. Keywords: Ointment, ointment base, ointment preparation method, ointment formulation, topical preparation, herbal extract.